ANALISIS PERAN STAKEHOLDER DALAM PENGEMBANGAN OBJEK PARIWISATA ALAM DAN SEJARAH DI KELURAHAN PAJARESUK KABUPATEN PRINGSEWU - A.Hidayah, Ni’mah; Hutagalung, Simon S.; Hermawan, Dedy (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2019)
Stakeholders are individuals or groups that are actively involved in activities that are affected by both positive and negative. The roles of stakeholders are needed by the three actors, the development of tourism can be done optimally. Each stakeholder involved has different influences and interests in accordance with their sphere and responsibilities, so that their involvement will provide different benefits in the implementation of tourism development. The results of this study are related to the stakeholders involved in the development of community, government, and private sectors, and stakeholders involved in tourism development have done various development both physical and non-physical development. Cooperation and communication between stakeholders is relatively good so that it accelerates the process of implementation of tourism development.